Improving Learning Outcomes by Using the STAD Type Cooperative Learning Model - Sari, Yani Muriyan; Khaira, Tazkira (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was motivated by the phenomenon of low learning outcomes for the History of Islamic Culture in class VII-3 MTsN 3 South Aceh. One of the contributing factors is that teachers still predominantly use the lecture method, so students become bored while learning. To improve student learning achievement, the STAD learning model can be used, among other things. This research uses two cycles of Class Action Research. The research was carried out in semester 2 of the 2019/2020 academic year. The subjects of this research were 23 students in class VII-3 MTsN 3 South Aceh, taken as a total sampling in the research. The data collection techniques used are observation, questionnaires and tests. Meanwhile, data collection instruments use observation sheets, questionnaires and test questions. Data analysis techniques are carried out collaboratively, namely collecting quantitative and qualitative data. The results of the research showed that there was an increase in teacher activity, 79% in the active category, 82.27% in student activity in the very active category, in student learning completion results there was also an increase reaching 82.60% with an average score of 77.60% and student responses of 93.97% in the very good category. This proves that using the STAD learning model in the History of Islamic Culture lesson can improve the learning outcomes of class VII3 MTsN 3 South Aceh students. This research is recommended to fellow teachers so that they can master and try to apply the STAD learning model, so as to create a lively, varied learning atmosphere and is proven to be effective in improving learning outcomes.